"Denial or Faith?" Therapy Versus Messianism in Preparing for the Evacuation of Israeli Settlements. (December 2015) - Plotkin Amrami, Galia
Abstract : This article offers an ethnographic account of the professional activities of mental health practitioners, employed by the state's religious education system. I analyze various models implemented by practitioners for the purposes of preparing pupils for the state‐mandated evacuation of Jewish settlers from Gaza and the West Bank. By focusing on the interaction between psychological and religious‐national cultural frameworks I show how practitioners imbue familiar professional concepts with new meanings and create hybrid models of intervention.